The Discrimination of Successive Sensory Impulses - Abel, Sharon Mildred (My University, 1967)
Preliminary experiments were conducted to evaluate a theoretical model for predicting temporal numerosity data. The model was based on a hypothetical central unit of duration. It described the gating of sequentially presented auditory pulses. Experiment 1 offered partial support for the prediction that events occurring within one unit 50 milliseconds in duration would be perceived as simultaneous. Results of Experiment 2 suggested that empty duration units occurring between sequential events would not affect number reported. The estimate of the unit was 60 milliseconds. Experiment 3, an attempt to improve methodology, suggested values of the unit of approximately 75 and 106 milliseconds.
Inadequacies of the model were discussed. Control experiments were considered to eliminate such cues for discrimination as duration and intensity differences.
Keywords: discrimination, successive sensory, impulses, intensity